The Influence Of Digital Marketing Implementation On Improving Management Accounting Performance In Retail Companies In Surakarta - Ramadhian Agus Triono Sudalyo Rama; Nurita Elfani Prasetyaningrum (CV. HEI PUBLISHING INDONESIA, 2024)
This study aimed to analyze the influence of digital marketing implementation on improving management accounting performance in retail companies in Surakarta. Data were collected through questionnaires distributed to 98 retail companies in Surakarta. The results of multiple linear regression analysis showed that the implementation of digital marketing had a significant positive effect on management accounting performance. These findings confirm that by implementing effective digital marketing strategies, retail companies can improve management accounting performance through the utilization of valuable analytical data on customer preferences, purchasing patterns, and the effectiveness of marketing campaigns. This study encourages retail companies to adopt digital marketing integrated with sound management accounting practices